The adenylate cyclase response to parathyroid hormone in cultured rabbit marrow fibroblastic cells. - Barling, P; Bennett, J; Triffitt, J; Owen, M (1989)
The ability of fibroblastic cells to respond to parathyroid hormone (PTH) by an increase in adenylate cyclase activity is accepted as a characteristic of the osteogenic phenotype. Whether marrow fibroblastic cells, which have osteogenic potential when assayed in vivo, demonstrate this hormonal response when cultured in vitro has been investigated. Our study has shown a level of stimulation of adenylate cyclase activity by PTH in cultured rabbit marrow fibroblasts comparable with other osteogenic cells in vitro. The effect is seen in fibroblasts grown either from multiple colonies or from single colonies. Only a proportion of colonies had osteogenic potential in vivo assay and our results show a similar finding for the PTH response in vitro. To what degree the two parameters are expressed by the same colony has not yet been established.